STANDARDIZATION OF PROCESSES AND QUALITY CONTROL IN COMMERCIAL KITCHENS (International Seven Journal of Multidisciplinary, 2022)
This article analyzes process standardization and quality control in commercial kitchens, considering their relationship with food safety, the organization of production routines and the qualification of the work performed by food handlers, the study was developed through a qualitative, bibliographic and descriptive approach, based on open access scientific articles published between 2018 and 2022, selected according to their relevance to the proposed theme, the discussion was structured around operational standardization, hygienic-sanitary control and the articulation between training, monitoring and continuous improvement, the results indicate that the formalization of work stages contributes to greater production regularity, supports the reduction of nonconformities and increases the predictability of operations in food services, it was also observed that meal safety depends on the integration of good practices, supervision, verification tools and monitoring of environmental conditions, it is concluded that quality in commercial kitchens is consolidated through defined routines, frequent monitoring and continuous team training, elements that strengthen sanitary compliance and the stability of the production process.